2010
DOI: 10.1111/j.1467-6419.2009.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Human Capital: A Retrospective Study of the Literature

Abstract: Abstract. Grossman proposed an individual's health can be viewed as one aspect of their human capital. Following this line of thought a number of recent papers have reported a positive impact of alcohol consumption on earnings. The rationale for the existence of such a relationship is the positive impact of alcohol on physical and mental health. We conduct a meta-analysis to determine whether such factors as: the estimation technique, the presence of ex-drinkers in the sample, possible sample selection bias an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 78 publications
(89 reference statements)
1
16
0
2
Order By: Relevance
“…Several studies in the economics literature have found that gender differences are present in the relationship between alcohol use and labor market outcomes (Berger and Leigh, 1988; Dave and Kaestner, 2002; Kenkel and Ribar, 1994; Mullahy and Sindelar, 1991, 1996, 1997). In addition, drinkers in general, and sometimes heavy drinkers, tend to have higher earnings compared to abstainers or light drinkers (Berger and Leigh, 1988; Bray, 2005; French and Zarkin, 1995; Hamilton and Hamilton, 1997; Heien, 1996; Lye and Hirschberg, 2010; Zarkin et al, 1998). Several explanations are possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the economics literature have found that gender differences are present in the relationship between alcohol use and labor market outcomes (Berger and Leigh, 1988; Dave and Kaestner, 2002; Kenkel and Ribar, 1994; Mullahy and Sindelar, 1991, 1996, 1997). In addition, drinkers in general, and sometimes heavy drinkers, tend to have higher earnings compared to abstainers or light drinkers (Berger and Leigh, 1988; Bray, 2005; French and Zarkin, 1995; Hamilton and Hamilton, 1997; Heien, 1996; Lye and Hirschberg, 2010; Zarkin et al, 1998). Several explanations are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol may be a marker for personality traits that contribute to higher earnings (Lye and Hirschberg, 2010). For example, alcohol is positively associated with sociability (Cook et al , 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it seems that low to moderate alcohol consumption is a proxy for a range of personality traits that have a positive influence on human capital. A recent meta-analysis of studies that had reported a positive effect of alcohol consumption on earnings found this to be an artifact: First, it appeared that those who consumed large amounts of alcohol were less likely to be employed and therefore not in the studies; second, when the proportion of the abstainers among the participants was less than 28%, there was no beneficial effect of alcohol on wages (this only became apparent when the proportion of abstainers was greater than 28% and likely to include ex-drinkers); and, third, when accounting for the potential simultaneity of alcohol consumption and wages, the meta-analysis found no level of alcohol consumption that had a positive effect on wages (Lye & Hirschberg, 2010).…”
Section: Heavy Drinking Patterns Cause Many Problems For Allmentioning
confidence: 95%
“…Adicionalmente, conforme Koch & Ribar (2001), o uso de álcool possui efeitos colaterais na escolaridade, pois tornam o investimento em educação menos produtivos. A perda de produtividade ocorreria, de acordo com Lye & Hirschberg (2010), através de perdas no estoque de saúde (física e mental) do capital humano.…”
Section: Consumo De áLcool Cigarro E Outras Substâncias Na Performanunclassified
“…Em termos empíricos, segundo Lye & Hirschberg (2010) e Cawley & Ruhm (2011, os efeitos do consumo de álcool, cigarro e outros tipos de drogas sobre os resultados educacionais têm sido frequentemente documentados na literatura internacional, especialmente as investigações sobre os impactos do uso de bebidas. Koch & Ribar (2001), a partir do painel de dados do NLSY 1979-1990 para pares de irmãos do mesmo sexo, encontram que as consequências do uso de bebidas alcoólicas na juventude sobre a educação é sensível as diferentes especificações econométricas.…”
Section: Consumo De áLcool Cigarro E Outras Substâncias Na Performanunclassified